Punishment in world history - Stearns, Peter N., author.
1 online resource.
Keywords: "This book focuses on major changes in punishment patterns during the principal phases of world history, tracing continuities, reforms, and regional differences. With far-reaching coverage of a variety of human civilizations in history, this book is a core resource for students and scholars of the history of corrections, world history, and criminal justice"--